Time for bed - Danot, Serge (Oxford University Press Oxford, 2005)
In association with the UK Film Council and Sky Movies, Pathe Films ("Chicken Run", "Girl with a Pearl Earring", amongst many others) produced "The Magic Roundabout", a full-length CGI film. This book shows the characters from "The Magic Roundabout" at various times of the day. It features a clock to enable effective learning of telling the time.